2020
DOI: 10.1177/0022243720910104
|View full text |Cite
|
Sign up to set email alerts
|

Advertising Effectiveness for Multiple Retailer-Brands in a Multimedia and Multichannel Environment

Abstract: An important aspect of multimedia advertising effectiveness that remains unexplored is a customer-level analysis of the relative importance of each medium for multiple retailer-brands within a product category. The increasing availability of customer databases for parent companies containing multimedia ad exposures, sales transactions in several purchase channels, and information across multiple retailer-brands now allows for a broader examination of advertising effectiveness. In this research, the authors mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 52 publications
2
46
0
1
Order By: Relevance
“…For example, Lawrence et al (2019) study profitability of multichannel strategies in business-to-business markets by using a mix of field data and experiments, and find evidence for synergistic effects between online and offline channels. Further, Danaher et al (2020) use customer-level data, which are widely available, to study multimedia advertising effectiveness for a multichannel retail environment to uncover cross-media and cross-channel competitive effects. Many new research issues emerge as the use of multiple channels becomes the norm for consumer, business, and services markets.…”
Section: Recent Trends In Jmr Publicationsmentioning
confidence: 99%
“…For example, Lawrence et al (2019) study profitability of multichannel strategies in business-to-business markets by using a mix of field data and experiments, and find evidence for synergistic effects between online and offline channels. Further, Danaher et al (2020) use customer-level data, which are widely available, to study multimedia advertising effectiveness for a multichannel retail environment to uncover cross-media and cross-channel competitive effects. Many new research issues emerge as the use of multiple channels becomes the norm for consumer, business, and services markets.…”
Section: Recent Trends In Jmr Publicationsmentioning
confidence: 99%
“…For instance, we would have liked to have had data that would enable us to provide direct evidence on the relative role of advertising to other margins of adjustments (e.g., pricing) as well as how operators allocate their overall advertising budget to different media types and other margins of adjustments (e.g., pricing and quality investment). Studying the intensive and extensive margin adjustments by firms (e.g., Danaher 2017;Danaher and Dagger 2013;Danaher et al 2020) in response to the changing cost advantage of mass advertising is an important area for future research because the technology of running "more local ads" has become available across all types of media from television to online advertising. Relatedly, future research is needed to investigate the potential differential roles and effects of national and local advertising, as well as possible substitutability and complementarity between them.…”
Section: Discussionmentioning
confidence: 99%
“…With the increasing availability of consumer datasets in all touchpoints and channels, the effectiveness of advertising in different media can be better evaluated. Danaher et al (2020) found that emails and sometimes catalogs exert negative effects on other retailer-brand sales in the category, and paid search only has effect on the focal retailer-brand sales. Consumers who shop across multiple retailer brands and both online and offline channels are the most responsive to multimedia advertising.…”
Section: Advertisingmentioning
confidence: 96%
“…Current studies on omnichannel advertising have investigated the effectiveness of omnichannel advertising practices (Danaher et al, 2020;Zhang et al, 2019). With the increasing availability of consumer datasets in all touchpoints and channels, the effectiveness of advertising in different media can be better evaluated.…”
Section: Advertisingmentioning
confidence: 99%